46 XY disorder of sex development (DSD) due to 5 alpha (SRD5A2) deficiency – Experience from a multidisciplinary Pediatric Gender Clinic. Issue 4 (August 2022) - Bose, Sumona; Das, Kanishka; George, Belinda; Raman, Vijaya; Shubha, A.M.; Mahadevappa, Kiran; Kumar, Prasanna; Bantwal, Ganapathi; Ayyar, Vageesh; Deb, Mainak
Summary: Background: SRD5A2 deficiency leads to incomplete masculinization of individuals with a 46 XY karyotype. A definitive diagnosis in early infancy facilitates decisions concerning choice of sex of rearing and management. Aim: To review the clinical presentation, diagnosis, treatment and outcome of children with 46 XY DSD due to SRD5A2 deficiency at a Paediatric Gender Clinic. Study design and methods: Retrospective review of cases of SRD5A2 deficiency (2000–15) managed with a standard protocol at a multidisciplinary clinic. Demographic data, clinical presentation, physical findings, investigations (hormonal profile, imaging, genitoscopy), psychological evaluation (child, family), medical and surgical management, outcome and follow up were collated and analyzed. Results: There were 12 cases aged 3 days–14 years at presentation, 3 had parental consanguinity. Eight were reared as males and 4 as females. Specialist referral was sought for hypospadias (5), atypical genitalia (5) or incongruent pubertal masculinization (2). All had chordee, symmetrical inguinoscrotal gonads, rugose labioscrotum and proximal hypospadias (perineoscrotal −9, perineal −3). Both pubertal cases had significant masculinization and no gynecomastia. The median testosterone/dihydrotestosterone ratio was 22.1(IQR-8.6-55.7). Despite a classical phenotype, four (2 prepubertal, 2 pubertal) had a ratio <10. Genitoscopy showed urogenital sinus remnant (4) and hypoplastic verumontanum (5). Sex reassignment was done in 4. Surgical management was staged and completed by 4 years in those with infantile presentation. Besides correction of chordee and urethroplasty in 11, other procedures included orchidopexy (5), excision of a urogenital sinus remnant (4) and correction of penoscrotal transposition (4). The urethroplasty was single staged in 3. All operated cases were followed up (mean age at last follow up - 10.63 years, mean follow up period - 7.25 years). The overall cosmetic result was satisfactory, but the phallic structure remained relatively small across prepubertal period. Uroflowmetry curves were normal in 9. All showed penile tumescence/erection and two peripubertal cases had typical secondary sexual characters. All cases, including those with sex reassignment, have a well-adjusted male psyche. Discussion and conclusion: The diagnosis, management and longitudinal follow up of cases of SRD5A2 deficiency at a multidisciplinary gender clinic is presented. Diagnostic dilemmas with low T/DHT ratios remained in a third of cases. Most were diagnosed in infancy and assigned a male sex of rearing, all underwent staged masculinizing genitoplasty. Those with sex reassignment also fared well with comprehensive management after family counseling.